Track Analysis of the North, Central and South American Species of the Epicauta maculata Group (Coleoptera: Meloidae) - Campos Soldini, Maria Paula (2015)
We undertook a panbiogeographic analysis of 23 species of the Epicauta maculata group of America—Epicauta abeona Pinto, Epicauta adspersa (Klug), Epicauta andersoni Werner, Epicauta atomaria (Germar), Epicauta apache Pinto, Epicauta cavernosa (Courbon), Epicauta dilatipennis Pic, Epicauta fulvicornis (Burmeister), Epicauta horni Champion, Epicauta jeffersi Pinto, Epicauta koheleri Denier, Epicauta lizeri Denier, E. maculata (Say), Epicauta magnomaculata Martin, Epicauta minutepunctata Borchmann, Epicauta nigropunctata (Blanchard), Epicauta normalis Werner, Epicauta ocellata (Dugès), Epicauta pardalis LeConte, picauta phoenix Werner, Epicauta pluvialis Borchmann, Epicauta proscripta Werner, Epicauta rubella Denier, and Epicauta ventralis Werner—with the purpose of analyzing the distributional data for taxa, to establish patterns of distribution of an ancestral biota and areas where these groups have interacted. Based on the overlap of 20 individual tracks, four generalized tracks constituted by different numbers of species were identified; two of them are located in the Nearctic region and the Mexican transition zone (tracks “A” and “B”), and the other two are distributed in the Neotropical region and the South America transition zone (“C”, “D”). Six nodes were recognized: Two of them are included in the Nearctic Region, node ‘I’ located in northern USA and node ‘II’ located in southwestern USA, both at the intersection of the tracks “A” and “B”. The other four are included in the Neotropical Region at the intersection of the tracks “C” and “D”: Node ‘III’ is located in Chaco province; node ‘IV’ is located in Parana Forest province; node ‘V’ is located in the northwest of Argentina in Puna province, and node ‘VI’ is located in Monte province.